1983
DOI: 10.1002/gj.3350180206
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade metamorphism within the Welsh sector of the paratectonic Caledonides

Abstract: Mineral assemblages within metabasites from the paratectonic Caledonides of Wales show that the grade of metamorphism was predominantly within the prehnite-pumpellyite facics, although greenschist facies assemblages occur in the more central parts of the region. General agreement with this pattern of metamorphism is Seen in recent studies of illite crystallinity and conodont colour. Comparison with other regions suggests that all of the paratectonic Caledonides of the British Isles has suffered a low-grade of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The rocks analysed in this study have all undergone low-grade sub-greenschist facies metamorphism (Bevins & Rowbotham, 1983; Robinson & Bevins, 1986) and this is reflected in the abundance of chlorite observed in the thin-sections along with less common pumpellyite, prehnite and epidote. Varying degrees of albitization have affected the rocks and so the concentrations of Al, Ca and Na in particular have been modified (Bevins, 1982).…”
Section: Geochemical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rocks analysed in this study have all undergone low-grade sub-greenschist facies metamorphism (Bevins & Rowbotham, 1983; Robinson & Bevins, 1986) and this is reflected in the abundance of chlorite observed in the thin-sections along with less common pumpellyite, prehnite and epidote. Varying degrees of albitization have affected the rocks and so the concentrations of Al, Ca and Na in particular have been modified (Bevins, 1982).…”
Section: Geochemical Resultsmentioning
confidence: 99%
“…(zeolite to low-grade greenschist facies) metamorphism, primarily due to burial (Bevins & Rowbotham, 1983;Bevins & Robinson, 1988;Robinson et al 1999).…”
Section: Local Geology and Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorpe et al (1991), in their comprehensive (but essentially geochemical) review of the geological sources and mode of transport of the Stonehenge bluestones, provided a very brief petrographic description of the dolerites and noted the anhedral form of the Preseli dolerite spots, their irregular/unsystematic distribution (from sometimes forming up to around 15% of a rock surface to only one spot being visible on an area of ca. 1 m 2 ) and their metamorphic mineralogy, and concluded that they represent porphyroblasts arising from the low-grade metamorphism described by Bevins and Rowbotham (1983) and . Thorpe et al (1991) did, however, describe for the first time the chemistry of the spots compared to the host dolerite, recording that the spots have markedly higher concentrations of Al 2 O 3 , Sr and CaO and greatly depleted concentrations of the incompatible elements Nb, Y and Zr when compared to the host dolerite.…”
Section: Previous Accounts Of the Spotted Doleritesmentioning
confidence: 96%
“…With the exception of early compaction (1 above) and the late illitization and pumpellyite replacement (7 above) which are probably attributable either to deep burial diagenesis or to a low grade regional metamorphic event thought to have affected this area (Bevins and Rowbotham 1983), the diagenetic sequence 2-6 is typical of marine volcanic sandstones (Almon ef af. 1979;Surdam and Boles 1979;Lee and De Vreis Klein 1986).…”
mentioning
confidence: 99%